Transição socioenergética para o desenvolvimento social: um estudo sobre comunidades rurais na região do Médio Solimões/AM - Carvalho, Willian Rodrigues (2022)
This study analyzes the effects of the socioenergetic transition in rural communities of the middle Solimões/AM. To this end, an extensive bibliographic and documental survey was carried out that showed the possibility of a socio-energetic transition towards a social (sustainable) development in the Amazonian rural context, as long as there is an understanding of the Amazonian socio-cultural characteristics, beyond technical or economic aspects. In addition, 30 semi-structured interviews were carried out with residents of the rural communities of Boa Vista(Tefé/AM) and Vila Soares (Uarini/AM), located in the region of Médio Solimões/Amazonas, who received electricity through the Light for All. One of the questionnaires on the perception of electric exclusion in rural Amazonian communities indicated that most of the family representatives participating in the study, in both communities, recognize the contribution of access to electric energy to better conditions for health care and education. Although they do not feel excluded from access to electric energy, they recognize flaws regarding the technical and institutional issues involved in the electrification process carried out in these places. Among the various uses of electricity, which could be verified through the questionnaire on the socio-energetic transition in these communities, the use of household appliances such as television, cell phone, freezer/refrigerator, and fan stand out. In this way, it becomes evident that the access to electric energy in rural areas may be able to supply everything from the need to inform and communicate, to better water and food storage. In addition, it also provides better access to water, making it possible to use pumps to pump water, as reported by the informants of this research. However, there are representatives of the families, who feel financially disadvantaged from the energy transition to a formal electric energy service in their community, due to the energy consumption fee that is charged at the end of the month. Considering the low economic profile, whose income comes mainly from social benefits like Bolsa Floresta and Bolsa Família, besides subsistence activities like agriculture. This shows the need for a political energy planning for rural Amazonia that can allow the democratic and equal participation of all involved. And thus, promote a local development that, besides the expansion of individual liberties, is indeed inclusive, sustainable and sustained.